(untitled) (International Journal of Nursing Education, 2022)
Cardiac arrhythmias are cardiac rhythm disorders that comprise an important epidemiological and public health problem. Objectives: The objectives of the study were to evaluate the effect of a Planned Teaching Programme on knowledge regarding identification and management of Cardiac Arrhythmias among staff nurses and find the association between the pretest knowledge level regarding identification and management of Cardiac Arrhythmias among staff nurses and the selected sociodemographic variables. Methodology: A quantitative research approach was used with quasi experimental design (one group pretest posttest design). The sample consists of 40 staff nurses, selected conveniently. Data were collected using the tools - socio-demographic data and structured knowledge questionnaire. Pretest was conducted on day 1. Planned Teaching Programme was given for 45 minutes on the same day. Posttest was conducted on day 14. Results: The paired ‘t’ test showed that the calculated ‘t’ value (12.37) was greater than the table ‘t’ value (3.55) which was significant at P < 0.001. There was significant association between the sociodemographic variable - area of working and the pretest knowledge level of staff nurses. Conclusion: Planned Teaching Programme is highly effective in improving the knowledge of staff nurses regarding identification and management of cardiac arrhythmias.